Review of sustainable finance-based financing regulations in Indonesia: Analysis of regulatory responses to global environmental financing developments - Muhammad Lazuardi Annas (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Indonesia is committed to lowering carbon emissions and supporting Environmental, Social, and Governance (ESG) principles to achieve sustainable development goals. This commitment is operationalized through regulations in the financial industry, such as requiring banks to fund green portfolios. This study analyzes how Indonesia’s current sustainable finance regulations respond to emerging global developments in environmental financing. Methods: This qualitative research utilizes a normative juridical approach, relying on library study to trace and analyze formal written legal texts. The analysis employs conceptual norm analysis to examine concepts within sustainable financing regulations. Theoretically, the regulations are analyzed using Yusuf al-Qaradhawi’s concept of environmental preservation (ra’iyah al-bi’ah). Findings: The research found that POJK 51/2017 offers a structured and ambitious response, aligning fundamentally with global ESG values through its eight Sustainable Finance Principles. This supports al-Qaradhawi's theory requiring enforceable legislation for environmental protection. However, the regulatory scope is limited compared to international benchmarks, and the administrative sanctions are considered inadequate for effective compliance. Conclusion: While establishing robust process-based mechanisms, such as the RAKB and mandatory Sustainability Reports, the effectiveness of Indonesian regulation is challenged by its weak enforcement and optional independent verification. Structural reforms are crucial to enhance regulatory credibility and meet stringent global environmental expectations. Novelty/Originality of this article: This study offers novelty by analyzing Indonesian sustainable finance regulations in direct response to the trajectory of global sustainable finance standards and taxonomies. Furthermore, it utilizes a unique theoretical framework by assessing the regulations based on Yusuf al-Qaradhawi's concept of environmental preservation (ra’iyah al-bi’ah). This integrated legal-theological assessment provides novel insight into the regulatory response to global demands.